The Success Evaluation of Platform Merdeka Mengajar (PMM) Implementation in Purbalingga Regency Using HOT-Fit Model - Abidin, Uun; Hariguna, Taqwa; Barkah, Azhari Shouni (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2025)
The industrial 4.0 revolution increasingly develops. It also affects the education field. This issue can be used to improve the quality of education by improving teachers quality. The Merdeka Mengajar platform (PMM) is used to improve the quality of teachers in implementing the Merdeka curriculum (Independent Platform). When it is implemented, teachers have difficulty to adapt the independent teaching platform and not all teachers understand technology. The purpose of this research is to analyze the factors that influence the successful implementation of the Merdeka Mengajar Platform (PMM) using the Hot fit method which assesses system success from the aspects of human, organization and technology. The research sample was 220 vocational high school teachers in Purbalingga Regency. The results of this research can be concluded that all variables contained in the Hot Fit model. They are Service Quality, System Quality and Information Quality, System Use and User Satisfaction. Structure and Environment have a positive and significant effect on the successful implementation of the Merdeka Mengajar Platform (PMM) used by vocational teachers in Purbalingga Regency. The Research Model in this study has a level of feasibility and accuracy of 71.6%, while the rest is influenced by other variables which is not included in this study. By this research, we can find out the factors that influence the successful implementation of the Merdeka Mengajar Platform (PMM) in Purbalingga Regency.